Analytic hierarchy progress (AHP) for construction technologies adoption in the Malaysian Construction Industry - Chai, Changsaar; Gai, Ming; Lee, Chia Kuang; Chong, Wan Siang; Wong, Mervyn Hsin Jyi (IGI Global Scientific Publishing, 2025)
Digital technologies are vital for boosting productivity and efficiency in Malaysia's construction industry. Despite a 74% awareness rate of Building Information Modeling (BIM) reported in the Malaysia BIM Report 2019, adoption remains limited. This study employs a quantitative methodology, using questionnaire surveys to assess the need for technology adoption among industry players. The findings aim to inform the development of a decision- making tool for selecting suitable technologies for construction projects. By identifying key challenges arising from limited digital adoption, the research proposes strategies to enhance technology integration. Expected outcomes include improved project outcomes, reduced cost overruns, minimized delays, and enhanced industry productivity. Ultimately, these advancements will contribute to Malaysia's GDP growth while addressing critical inefficiencies in the construction sector. Promoting digital adoption is essential for elevating the industry's performance and ensuring its long- term sustainability.